Implementation of Labor Overtime Protection of PT Hwaseung Indonesia - Metry Widya Pangestika; Arpangi Arpangi (Law Development Journal, 2020)
This study is based on the legal problems of the workforce who work overtime hours at PT Hwaseung Indonesia. This research uses empirical juridical law research methods aimed at analyzing the implementation of legal protection of overtime work of PT Hwaseung Indonesia. Legal protection at PT HWI has not been fully implemented in accordance with Article 78 letter b of the Employment Law No.13 of 2003 that is, overtime work can be done a maximum of 3 hours in 1 day, and 14 hours in 1 week. Kepmen. No. 233 / MEN / 2003 allows its employees to work beyond the provisions of Law No. 13 In 2003, the original work was done according to the type and nature must be continuous. Although there are violations of overtime hours, the implementation of legal protection against workers beyond overtime has been done by PT. HWI, that is, by requesting the consent of workers before committing overtime and providing overtime wages. It is hoped that through this research will be found new ideas of thought that are useful for the Indonesian Ministry of Transport. Where the results of the research can be used as an indicator in conducting labor surveillance, in order to find ideas on how labor regulations play a greater role for the human rights of workers.